ENGAGEMENT, OUTREACH, AND ICTD : TOWARDS DEVELOPED ISLAMIC HIGHER-EDUCATION INSTITUTION - Arsyad, Azhar (Journal of Islam and Science, 2014)
As we know that higher education institutions (HEIs) have three main mandates—teaching, research, and extension. The first refers to the transmission and transaction of knowledge, skills and competencies to learners so as to equip them for their role in the employment market and society. The second refers to the critical role of advancing knowledge through research in different domains. The third refers to the institution reaching out to the community in which it is located, providing the community with a valuable contribution to social development. Outreach and engagement at the higher-education Institution is that aspect of teaching that enables learning beyond the campus walls. That aspect of research that makes what we discover useful beyond the academic community. That aspect of service that directly benefits the public. When the Islamic discourse comes under discussion, the concept should be applicable to the cultural discourse, the literary discourse, the artistic discourse and the information discourse, though the latter can be of more comprehensive nature and encompass all other levels of discourse, in such a way as to become for example the religious information discourse, the philosophical information discourse, the political information discourse, etc. In terms of using ICT or media, the content, again as mentioned before using all media forms, should seek to promote dialogue, understanding, co- existence and co-operation.